Exploring the mediating role of social capital in the relationship between financial intermediation and financial inclusion in rural Uganda - Okello Candiya Bongomin, George; Munene, John C.; Mpeera Ntayi, Joseph; Akol Malinga, Charles (International Journal of Social Economics, 2018)
The purpose of this paper is to establish the mediating role of social capital in the relationship between financial intermediation and financial inclusion in rural Uganda. Design/methodology/approach – The current study used cross-sectional research design and a semi-structured questionnaire was used to collect data for this study. The study applied structural equation modeling through bootstrap approach in AMOS to establish the mediating role of social capital in the relationship between financial intermediation and financial inclusion. Findings – The results indicated that social capital significantly mediates the relationship between financial intermediation and financial inclusion in rural Uganda. Therefore, it can be deduced that social capital among the poor play an important role in promoting financial intermediation for improved financial inclusion in rural Uganda. Research limitations/implications – Although the sample was large, it may not be generalized to other segments of the population. Data were collected from only poor households located in rural Uganda. Besides, the study was cross-sectional, thus, limiting efforts in investigating certain characteristics of the sample over time. Perhaps future studies could adopt the use of longitudinal research design. Practical implications – Financial institutions such as banks should rely on social capital as a substitute for physical collateral in order to promote financial inclusion, especially among the poor in rural Uganda. Originality/value – This study provides empirical evidence on phenomenon not studied in rural areas in Sub-Saharan Africa where the poor use social capital embedded in customs and norms for doing business. The results highlight the importance of social capital in mediating the relationship between financial intermediation and financial inclusion of the poor in rural Uganda.
Keywords: Financial inclusion; Social capital; Structural equation modelling; Mediation effect; Financial intermediation; Rural Uganda